Growth of TiO2 microspheres with a radially oriented configuration. Issue 32 (2nd August 2017) - Truong, Quang Duc; Kato, Hideki; Kobayashi, Makoto; Kakihana, Masato
Abstract : Hierarchical microspheres constructed from radially oriented TiO2 nanorods have been fabricated. The obtained three-dimensional mesoporous TiO2 microspheres have a high accessible surface area (66 m 2 g −1 ), large pore volume (0.15 cm 3 g −1 ), and well single-crystallized rutile nanorod walls. Abstract : Crystalline mesoporous materials with oriented configurations are promising for high-performance energy storage and conversion devices. In this work, hierarchical microspheres constructed from radially oriented single-crystalline TiO2 nanorods have been fabricated by a facile hydrothermal approach using oxalic acid as a chelating and structure-directing agent. The obtained mesoporous TiO2 microspheres have been characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy and Brunauer–Emmett–Teller specific surface area measurement to reveal their unique properties. The growth and assembly process of the nanorod-based microspheres were elucidated in view of chelation-assisted assembly. It was found that oxalic acid played a crucial role in the oriented assembly of nanorods into well-defined microspheres.